DAMPAK PEMEKARAN WILAYAH PASCA KONFLIK (Studi Kasus Desa Bale dan Desa Ori) - Jefri Balamu; John R Lahade (Cakrawala Jurnal Penelitian Sosial, 2019)
The objective of this study is to examine the couses of expansion Ori and Bale villages andthe impacts on the two communities viewed as economic, socio-cultural and socio politics.The type and the approaches of this research is a qualitative-descriptive methods. Theresult of this research shows that expansion of ori and bale villages are governmentprogram for the formation of a new district, but this expansion is still based on acompetation sense from the conflic. After reconciliation relationship of two communitiesof religion in bale is not fully running away. As of goverment given a tennder forexpanxion bale villages and than comunity of two religion agree with this tendder. thatthe distribution as if by religion. while the impact this expansion had a negative impacton the economic ,social culture and socio politics of the villages. Results of this study haveimplications for the necessity to both the villagers and the government to improve thequality of life after splitting both economic, socio-cultural and socio politics.Keywords: conflic, reconciliation, villages expansion, social impact.